P08.09 RADIOSURGERY FOR BRAIN METASTASES: PROSPECTIVE VALIDATION OF THE BSBM PROGNOSTIC SCORE - Devriendt, D. (Oxford University Press, 2014)
PURPOSE: To prospectively validate our basic score for brain metastases (BSBM) classification in patients treated by Gamma Knife radiosurgery (GKRS) for brain metastases (BM) METHODS AND MATERIALS: Between January 2003 and December 2007, we treated more than 1000 BM in 283 patients by RS. We followed these patients prospectively since January 2003 using the BSBM classification, which is based on 3 prognostic factors: no extracranial metastatic disease (ECMD), KPS ≥80, primary tumor controlled. A score of 0 to 1 point was attributed to each factors, with a total from 0 to 3 points; the patients had a BSBM score 0, 1, 2 and 3 in 2.5%, 13%, 60% and 24%, respectively. RESULTS: The median survival (MS) was 12 months (95% CI, 10-14 months); the 2-years and 5-years survival were respectively 27 and 10 %. The MS was 2.5, 6, 12 and 20.5 months respectively for the BSBM scores 0, 1, 2 and 3 (p < 0.001); the MS was respectively 13 and 11 months with an ECMD absent or present (p < 0.001), 4 and 13 months according a KPS <80 or ≥80 (p < 0.001) and finally, 13 and 7 months with a primary tumor controlled or not (p < 0.001). All 3 prognostic factors used in the BSBM classification were found statistically significant in univariate and multivariate analysis. CONCLUSIONS: We have validated prospectively our BSBM prognostic model which we developed retrospectively in 2004. The strenghts of our classification is the ease to use as we consider only 3 prognostic factors.